2009
DOI: 10.1111/j.1524-4725.2009.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Mohs Micrographic Surgery and Surgical Excision for Small Nodular Basal Cell Carcinoma

Abstract: http://www.clinicaltrials.gov Identifier: NCT00571363. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 11 publications
1
60
0
5
Order By: Relevance
“…This process is continued in a repeating fashion until the tissue section(s) show no histologic evidence of residual tumour. 45 The process can be time-consuming, requires specialized training, and although it can be cost-effective, is still costly. MMS results in cure rates as high as 99% and 96% for primary and recurrent tumours, respectively.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
“…This process is continued in a repeating fashion until the tissue section(s) show no histologic evidence of residual tumour. 45 The process can be time-consuming, requires specialized training, and although it can be cost-effective, is still costly. MMS results in cure rates as high as 99% and 96% for primary and recurrent tumours, respectively.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
“…In a small randomized trial, Muller et al reported that defect size after MMS for nodular BCC was significantly smaller (P \.001) than after standard excision (116.6 vs 187.7 mm 2 ). 50 Smeets et al reported that for tumors requiring more than 1 standard excision, or at least 2 stages of MMS, defects after excision were significantly larger than after MMS for primary and recurrent BCC. 33 Although smaller defects did not lead to significant differences in aesthetic outcome between MMS and standard excision in RCTs, both surgical modalities were found to be superior to C&E with regard to quality of life outcomes.…”
Section: Standard Excisionmentioning
confidence: 99%
“…Man ender som regel opp med en mindre huddefekt enn etter vanlig eksisjon -dermed kan man anvende enklere rekonstruksjonsmetoder (19,21). Huddefekten lukkes med primaersutur eller tilheler sekundaert.…”
Section: Mohs' Kirurgiunclassified
“…Ved at tumorutløperne forfølges trinnvis, oppnås radikalitet i tilnaermet alle tilfellene, samtidig som man sparer friskt vev. Huddefekten er som regel mindre enn etter vanlig eksisjon, og enklere rekonstruksjonsløsnin-ger kan velges (19,21).…”
Section: Vevssparendeunclassified